Semântica textual e representação arquivística: parâmetros e estruturas para elaboração de um modelo ideal - REIS, Lauson Favacho de Souza (2018)
Archival representation is part of a recent theoretical-conceptual development within the scope of Archivology, which aims at the integration of classification and description activities, as part of a single process of representation and accessibility to archival documents. The aim of this research is the use of semantic criteria to be adopted in the organization of archives, contributing in a systematic way to the construction of a theoretical and methodological reference around the archival representation. For this purpose, we have as a research methodology textual semantics, aiming at the deep analysis of textual productions from the descriptors of the research instruments of the observed archival institutions. The Brazilian archival tradition will be part of the delimitation of the corpus of practical-theoretical analysis. We work with two distinct archival institutions, the Arquivo Público Mineiro (APM) and the Arquivo Nacional Brasileiro (AN). The study of these institutions will comprise the micro-universe of the project "The Archival Representation: elements for the construction of an ideal teaching model through textual semantics from the Australian, Canadian and Brazilian contexts". We obtained as results, strong indicators of subjectivism in the descriptions of the inventories of private funds, as well as relative absence of connectivity between inventories of the same institution. It is hoped that, through the proposed theoretical systematization and the ideal teaching model to be created, this work will help consolidate the archival representation as a methodological approach in the Brazilian archival tradition.